Efeito fotoelétrico: uma abordagem a partir do estudo de circuitos elétricos - Cabral, Júlio César (2015)
The relevance of Modern and Contemporary Physics in today’s society is an indisputable fact. Therefore, the school with a perspective to form critical citizens, inserted into a highly technological society, need to rethink their current resumes, training teachers and indicating horizons of the new century to their students. In the present work we aim to insert modern physics content in high school by producing a potentially significant material, anchored in the cognitive theory of meaningful learning of Ausubel. For this purpose we choose to approach the Photoelectric Effect, since it appears in several technological applications, which are the living of the students. Furthermore, its phenomenology consists of one of the landmarks of the birth of Modern Physics, presenting a mathematical formulation, relatively simple and compatible with the high school student profile. As a way of introducing the content, an investigative experiment on the subject is used in order to awaken students’ curiosity. Soon after the experiment, students will take science theme through a didactic sequence (activities scripts) involving videos, reviews, lectures, concepts maps and virtual experiments tours carefully elaborated in ascending order of difficulty. The didactic sequence was applied in a class of third year of Guadalupe High School in Lagoa da Prata - MG. The results are shown and discussed throughout the study. The didactic sequence proposal may help the teacher in choosing the possible approach strategies of the subject, either through their lectures, or by the use of scripts based on Information and Communication Technologies. These scripts were developed in order to facilitate, challenge and promote understanding of the content by the students.